Organic Materials Promote Rhododendron simsii Growth and Rhizosphere Soil Properties in a Lead–Zinc Mining Wasteland - Yunchun Chen; Wei Li; Xinchen Cai; Bo Li; Fangdong Zhan; Yanqun Zu; Yongmei He (Plants, 2024)
The mining of metal minerals generates considerable mining wasteland areas, which are characterized by poor soil properties that hinder plant growth. In this study, a field plot experiment was carried out in the mining wasteland of the Lanping lead–zinc mine in Yunnan Province to study the effects of applying three organic materials—biochar (B), organic fertilizer (OF), and sludge (S)—at concentrations of 1% (mass fraction), on promoting the soil of mining wasteland and the growth of two plant varieties (Huolieniao and Yingshanhong). The results showed that the amount of available nutrients in the surface soil of a mining wasteland could be considerably increased by S and OF compared to the control check (CK). In the rhizosphere soils of two Rhododendron simsii varieties, the application of S increased the available phosphorus (P) content by 66.4% to 108.8% and the alkali-hydrolyzed nitrogen (N) content by 61.7% to 295.5%. However, the contents of available cadmium (Cd) and available lead (Pb) were reduced by 17.1% to 32.0% and 14.8% to 19.0%, respectively. Moreover, three organic materials increased the photosynthetic rate and biomass of two R. simsii varieties. Specifically, OF and S were found to significantly increase the biomass of R. simsii. Organic materials have direct impacts on the increased plant height and biomass of R. simsii. Additionally, organic materials indirectly contribute to the growth of R. simsii by reducing the content of available Cd and available Pb in rhizosphere soil while increasing the content of available nutrients according to the structural equation model (SEM). Overall, S can stabilize Cd and Pb, increase soil nutrient contents, and promote the growth of R. simsii effectively, and has great potential in the vegetation reconstruction of mining wasteland.